Quantitative determination of titanium tetrachloride and dichloromethane by Raman spectroscopy using carbon disulfide as an internal standard. Issue 7 (5th February 2020) - Xiang, Xiaoyan; He, Xianda; Xia, Wentang; Yin, Jianguo; Yuan, Xiaoli; Zhou, Xuejiao
Abstract : Raman spectroscopy with an internal standard and peak height ratio was applied for the quantitative analysis of dichloromethane and titanium tetrachloride. Abstract : An analytical method for the quantitation of titanium tetrachloride and dichloromethane in their mixtures was established by Raman spectroscopy. A cheap glass sampling pipe was used as a carrier for Raman spectroscopy measurements. The Raman peak height of carbon disulfide was used as the internal standard to remove interference factors such as sampling pipe diameter, temperature, laser power and other effects from the instrument. The peak height ratio between the Raman characteristic line of titanium tetrachloride or dichloromethane and that of carbon disulfide was proportional to the analyte concentration. The equation of the standard curve was y = 0.02028 + 5.04909 x with an R 2 of 0.9986 at the 387 cm −1 band for titanium tetrachloride determination. And the equation of the standard curve was y = 0.00097 + 0.26647 x with an R 2 of 0.9975 at the 706 cm −1 band for dichloromethane determination. The concentration of standard samples was calculated using these standard curves and the reproducibility was good with an RSEP value of 4.25% and 2.59% respectively for determining titanium tetrachloride and dichloromethane concentration. The established method was used to analyze the concentration of titanium tetrachloride and dichloromethane in samples obtained from the gas–liquid equilibrium still. These results were in good agreement with results obtained by infrared spectroscopy.